The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1177/0267659117720988
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular repair of subclavian artery aneurysms: results from a single-center experience

Abstract: For patients with SAAs, endovascular treatment is a feasible choice, with a high success rate, few complications and good clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Covered stent occlusion was found in one case at 16 months and the patient refused a reintervention because his upper limb ischemia was tolerable. 9 In addition, instent thrombosis requiring a reintervention at 1.5 months was noted by Archie et al 7 In general, based on our experience, despite that covered stent occlusions after endovascular treatment for ISAAs are not that uncommon, most patients could tolerate the ischemia with conservative treatment and reinterventions are not always necessary whether the occlusions occur in the short or long term.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Covered stent occlusion was found in one case at 16 months and the patient refused a reintervention because his upper limb ischemia was tolerable. 9 In addition, instent thrombosis requiring a reintervention at 1.5 months was noted by Archie et al 7 In general, based on our experience, despite that covered stent occlusions after endovascular treatment for ISAAs are not that uncommon, most patients could tolerate the ischemia with conservative treatment and reinterventions are not always necessary whether the occlusions occur in the short or long term.…”
Section: Discussionmentioning
confidence: 63%
“…Only several cases with the follow-up period longer than 36 months have been reported in isolated small case series. 7,9 A larger cohort with long-term follow-up remains scarce. To the best of our knowledge, Archie et al reported the longest follow-up period in the published data of 60 months in one patient after covered stent exclusion of an ISAA caused by arterial thoracic outlet syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endovascular repair of SAAs is case-dependent. In some complex cases, the neck of the aneurysm is close to the proximal end of the subclavian artery, and a stent graft can be implanted using the simultaneous kissing stent technique to maintain the blood flow of the right subclavian and carotid arteries and to prevent a type 1 endoleak ( 10 ). Furthermore, in cases where the SAA is located in the arterial branches, a combination of stent graft and coil embolization has been applied for endovascular treatment ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most cases are treated by open surgery (2,3). With advances in interventional techniques, endovascular repair has been suggested as a less invasive alternative to surgery (4)(5)(6)(7)(8)(9)(10). However, technical and anatomical considerations complicate the treatment of SAAs and pose some challenges.…”
Section: Introductionmentioning
confidence: 99%